Մեծ Հայքի Գուգարք նահանգն ըստ Է դարի «Աշխարհացոյց»-ի - Յակոբեան, Ալեքսան (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The Armenian geographical work “Ashkharhac'oyc'”, which was created for use by members of the Armenian delegation as an auxiliary material at the so-called Persian Council in Ctesiphon (616 or 618), gives a rather detailed description of the province of Gugarq (graec. Γωγαρηνή). According to this description, Gugarq consisted of 9 regions (gavars), which were separated from the Armenian country and included in the neighboring marzpanat of Iberia (Virq, Qartli) at the end of the 4th century. However, in the description of Iberia, 12 regions are listed that were torn away from Armenia. We associate this phenomenon with the main Bdešx (the Kurfyurst) function of the region of Tashir, who for this received rights over three additional regions (Bołnopor, Quishapor and Mangleac'por). A careful study of the text of “Ashxarhac'oyc'” makes it possible to clarify the localization and boundary lines of several regions of Gugark, which were previously proposed by Suren Yeremyan and Babken Harutyun-yan. This is especially true for the regions of Kangarq, Trełq, Tsobopor, Bołnopor and Quishapor. The article is accompanied by a map of Gugarq, which was compiled with the help of Ruben Tarumyan.
Keywords: Հայագիտություն; Աշխարհագրություն